Revolutionizing Agrotechnology: Meeting Global Food Demand through Sustainable and Precision Farming Innovations - Gusti Rusmayadi; Dwi Retno Mulyanti; Ali Zainal Abidin Alaydrus (Westscience Press, 2023)
Indonesia's status as the world's fourth most populous country underscores the importance of its contribution to global food security. However, this important role comes with a series of challenges that are exacerbated by changing climate dynamics, decreasing arable land, and the inherent inefficiencies of traditional farming techniques. Balancing the need to increase productivity with the imperative to preserve the environment is a formidable challenge that necessitates a paradigm shift in agricultural practices. However, these benefits are accompanied by barriers such as knowledge gaps, financial constraints, and infrastructure limitations, which need to be effectively addressed to utilise the full potential of these technologies. This research underscores the need for a holistic and context-sensitive approach. Effective knowledge dissemination, customised financing mechanisms, improved infrastructure, and supportive policy frameworks are essential to foster the adoption and implementation of innovative practices. In addition, the research highlights the importance of collaboration among various stakeholders, including farmers, policymakers, researchers and industry players, to collectively address challenges and capitalise on opportunities. The implications of this research extend beyond the borders of Indonesia. The findings provide insights that resonate with other developing countries facing similar challenges in agricultural transformation. By bridging knowledge gaps, promoting equitable access to technology, and fostering an enabling policy environment, countries can unlock the potential of the agrotechnology revolution to meet global food needs while maintaining the ecological balance of our planet. As the world grapples with the challenges of food security in an era of climate change, this research contributes valuable knowledge to build a more sustainable and resilient future for agriculture and humanity.